Cardioprotective effects of coffee - Anna Karaś; Kinga Kawałko; Kamil Pondel; Krzysztof Bielewicz (Kazimierz Wielki University, 2022)
Coffee is one of the most consumed beverages among adults. Popular for its stimulant properties, it is also appreciated for its taste and is an essential part of many people's daily lives. Coffee, in addition to caffeine, contains macroelements such as sodium, potassium and magnesium, which ensure the proper functioning of the body, as well as polyphenols which are characterised by their anti-inflammatory properties. [1,2] Atrial fibrillation is the most common arrhythmia and caffeine is often considered a potential risk factor. [3] The purpose of this article is to evaluate current scientific reports on the relationship between coffee consumption and atrial fibrillation.